INVESTIGATION OF CONSTANT SELF CONFIDENCE LEVEL OF HIGH SCHOOL STUDENTS WHO PARTICIPATE IN TEAM AND INDIVIDUAL SPORTS - Tayfun Kara (ümit doğan üstün, 2017)
The aim of this study was to examine the sportive self-confidence of high school students who engage in regular sports in terms of various variables. 210 high school students, who were randomly chosen, from Kutahya, voluntarily participated in the study. In the study, to collect data, in addition to a five items questionnaire which was developed by the researchers, "Constant Self Confident Scale", which was adapted to Turkish by Yıldırım (2013) was used. In the analyses of the data in order to identify significant differences between participants' constant self-confidence, independent samples t-test and two-way ANOVA was used. As a result, it was found that the participants' sportive constant self-confidence was higher in women and participants who engage in individual sports. But, these levels were found to be moderate when considering the points that can be taken from the whole scale. Also, there was a significant difference in favor of those who professionally play sports.